(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
batch arrival non-Markovian queue system in where consumers arrival are batches in accordance with Poisson process and customer are treated by first-comefirst- served principle. When a customer’s service is completed, he or she has the choice of requesting reservice for the same service or exiting the mode. Each customer’s service duration follows a genaral (arbitrary) distribution. In addition, after completing service, server takes vacation by having probability p or may be remain with probability 1−p, if any, to serve a subsequent customer. One of the impatient customers behavior balking, has also been added, indicating that a consumer can choose whether or not to enter the system. Also, we suppose after every period the server could not begin to providing service immediately, but rather requires some startup time before giving service to the first consumer. After discussion of transiant steady state system we can obtain closed-form system performance measurements